Implementation of Good Manufacturing Practices (GMP) in the processing of dried anchovy (Stolephorus spp.) at PT Insan Citraprima Sejahtera, Tuban, East Java - Nurhasyimi, Annisa Rizki; Patmawati, P (Genbinesia Journal of Biology, 2024)
The drying process for anchovy is a preservation method aimed at minimizing spoilage risks in this highly perishable food product by reducing its water content. To ensure safety and quality, Good Manufacturing Practices (GMP) is implemented in dried anchovy processing to prevent or mitigate contamination risks. This study evaluates the implementation of GMP in the processing of dried anchovies (Stolephorus spp.) at PT Insan Citraprima Sejahtera, located in Tuban, East Java. A descriptive research approach was utilized, with data collected through observations and interviews. The findings demonstrate that PT Insan Citraprima Sejahtera effectively applies GMP at all stages of dried anchovy processing, as evidenced by well-defined procedural standards, adequate facilities and infrastructure, and rigorous quality control supervision. The resulting dried anchovy products meet the quality standards stipulated in SNI-3461:2019